2019
DOI: 10.3390/cancers11020259
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Dosimetric Study of Radiotherapy Patients with Left-Sided Breast Cancer; Patient Selection Criteria for Deep Inspiration Breath Hold Technique

Abstract: Background: Several studies have investigated cardiac dose reduction when utilizing the deep inspiration breath hold (DIBH) technique in patients undergoing radiotherapy for left-sided breast cancer. This paper aims to recommend potential selection criteria based on a retrospective single institute study of free breathing (FB) and DIBH computed tomography (CT) simulation planning scans. Methods: Dosimetric comparisons were performed retrospectively for 20 patients correlating the dose reduction and patient ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
2
32
2
Order By: Relevance
“…It has been reported that variations in chest shape can impact the cardiopulmonary dose received. 37,38 In the present study, there was a positive correlation between the MHD and DHL. The patients with DHL ≥ 2.47 cm were associated with higher MHD compared to those lower DHL.…”
Section: Discussionsupporting
confidence: 61%
“…It has been reported that variations in chest shape can impact the cardiopulmonary dose received. 37,38 In the present study, there was a positive correlation between the MHD and DHL. The patients with DHL ≥ 2.47 cm were associated with higher MHD compared to those lower DHL.…”
Section: Discussionsupporting
confidence: 61%
“…However, we detected no variation between EBRT and IORT with numerically similar risk differences ( Figure 6), which leads to the conclusion that the effect may be independent of the applied technique. Given the extensive efforts in modern radiation oncology of keeping the heart doses as low as possible using different techniques, like cardiac shielding and deep-inspiration breath hold (DIBH), we anticipate the difference to be lower than estimated here [57]. Unfortunately, an analysis of NBCD or cardiac death divided by laterality of breast cancer was not possible.…”
Section: Discussionmentioning
confidence: 83%
“…As such, there is a need to prospectively identify patients who will dosimetrically benefit from DIBH. Anatomic factors such as tumour bed location, lung volume, and the distance of the heart from the chest wall can optimise the selection of patients for DIBH during left-breast radiotherapy, without the need for a CT scan during DIBH [36, 37]. Future studies are required to identify and validate appropriate selection criteria for the use of DIBH during right-sided breast radiotherapy.…”
Section: Discussionmentioning
confidence: 99%